Chemical looping combustion of biomass for renewable & non- CO2 emissions energy- status and review - Venkata Siva Naga Sai, Goli; C Pundlik, Rajat; Venkateswara Rao, p; R Kale, Ganesh (International Journal of Engineering and Technology, 2018)
World depends on fossil fuel combustion for thermal energy generation. Fossil fuel combustion leads to the generation of CO2 and extinction of non-renewable resources. To meet the future energy demands replacement of existing technologies should take place in the view of large quantities of GHG’s emissions from fossil fuels and their extinction. Chemical looping combustion (CLC) is primarily a combustion technique with an inherent separation of CO2 from the flue gases. Due to its advantage of negativeCO2 emissions, chemical looping combustion got attention of many researchers since last one and half decade. Recent research advancements in the CLC provided a platform for further research and developments in chemical looping combustion of biomass. This paper reviewsthe CLC of biomass to present the overview of chemical looping combustion technology and its status of biomass utilization as a fuel in CLC reactors.